DUKUNGAN SOSIAL PASANGAN TERHADAP MOTIVASI MENONTON SEPAK BOLA PADA SUPORTER PSIS SEMARANG - Prakasa Agif Pramudya; Ratriana Yuliastuti Endang Kusumiati (Journal of Innovation Research and Knowledge, 2026)
This study aims to determine the relationship between partner social support and the motivation to watch football among PSIS Semarang supporters. The participants consisted of 40 PSIS Semarang supporters who have partners and actively watch football matches using was accidental sampling. Data were collected using a partner social support scale adapted from the Social Support Questionnaire and a motivation to watch football scale based on Self-Determination Theory. The results showed a significant positive relationship between partner social support and the motivation to watch football among PSIS Semarang supporters (r = 0.503; p < 0.05). Partner social support contributed effectively by 25.3% to the motivation to watch football. These findings indicate that partner support plays an important role in increasing supporters' motivation to watch football matches.